2016
DOI: 10.1111/jocn.13262
|View full text |Cite
|
Sign up to set email alerts
|

Participation of family members and quality of patient care – the perspective of adult surgical patients

Abstract: The results emphasised the importance of family members for the patients in surgical care. Family members' participation is connected with the quality of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Engaging in a trialogue focuses on cooperation between these three groups and provides a new way to involve all stakeholders who are focused on important individual issues, relevant information, guidance, and care. Our findings complement other research findings that health care workers should share the right information and use open communicative tools to uncover the uniqueness of each patient and family . Using a trialogue, health care workers could meet the needs of both patients and relatives while helping them make the right choices and become aware of possibilities and demands along the care pathway, thereby appearing much more accommodating, trustful, and caring.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Engaging in a trialogue focuses on cooperation between these three groups and provides a new way to involve all stakeholders who are focused on important individual issues, relevant information, guidance, and care. Our findings complement other research findings that health care workers should share the right information and use open communicative tools to uncover the uniqueness of each patient and family . Using a trialogue, health care workers could meet the needs of both patients and relatives while helping them make the right choices and become aware of possibilities and demands along the care pathway, thereby appearing much more accommodating, trustful, and caring.…”
Section: Discussionsupporting
confidence: 81%
“…At the same time, they occasionally felt pressure to include their relatives in their care to meet health care system demands. A Finnish study reported similar findings—the authors describe patients’ and their families’ need to be together, but also that family involvement is beneficial to patients’ outcomes and in reducing health care costs . Based on this knowledge, other researchers have developed various models to inspire health care workers to focus on communication, the environment of care, and involving patients and their relatives…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…30 In studies utilizing the instruments separately, EKhp has been used for heart failure patients scheduled for cardiac resynchronization therapy implantation in Iceland 57 and for patients with cancer, 58 knee osteoarthritis, 59 and prostate cancer in Finland. 60 RKhp has been used in Finland for patients in ambulatory surgical nursing, 31 total joint arthroplasty, 32 surgical nursing, 55,61,62 medical wards, 63 and for family members and nurses in surgical nursing. 61 Two parallel instruments to EKhp and RKhp have been used to discover expected knowledge (EKso) and received knowledge of significant others (RKso) ( Table 1).…”
Section: Dovepressmentioning
confidence: 99%
“…[64][65][66][67][68] The respondents in the national studies (n=53-480, Table 2) were adult surgical patients, representing both genders, with a mean age of 44-72 years (SD 9-17), mostly employed (12-77%) or retired (17-85%). 16,[28][29][30][31][32][57][58][59][60]62,63 In all of the studies, validity and reliability of EKhp and RKhp have been evaluated, content validity has been confirmed by experts, and internal consistency of the instruments has been sufficient. Internal consistency of the EKhp instrument has been reported in several studies with Cronbach's alpha ranging from 0.80 to 0.98 and subscales between 0.77 and 0.96, [28][29][30][58][59][60] while that of the RKhp instrument has been reported to range from 0.80 to 0.99, and subscales between 0.76 and 0.98 (Table 1).…”
Section: Dovepressmentioning
confidence: 99%